Noise Sensitivity and Multiple Chemical Sensitivity. (December 2013) - Heinonen-Guzejev, Marja; Koskenvuo, Markku; Mussalo-Rauhamaa, Helena; Vuorinen, Heikki S.; Heikkilä, Kauko; Kaprio, Jaakko
Noise sensitivity is a personality trait covering attitudes to noise in general. Multiple chemical sensitivity (MCS) is the most commonly used label for clinical chemical intolerance. This study aimed to investigate if the Weinstein's Noise Sensitivity Scale and Quick Environmental Exposure and Sensitivity Inventory's (QEESI) Chemical Intolerance Subscale differentiate noise sensitivity and MCS as different entities. In 2002, 327 individuals (166 men, 161 women; age range 45–66 years) from the Finnish Twin Cohort answered a questionnaire. Factor analyses of the questionnaire items indicated the presence of three factors - Noise Sensitivity, Chemical Sensitivity, and Ability to Concentrate factors. Among all subjects, the Noise Sensitivity Factor was associated with neuroticism and smoking, and the Chemical Sensitivity Factor was associated with allergies and alcohol use. The study indicates that the Weinstein's Noise Sensitivity Scale and QEESI's Chemical Intolerance Subscale differentiate noise sensitivity and MCS as different entities.